Early school leavers' perspectives on the school dropout phenomenon in Zimbabwe - Omidire, Margaret Funke (University of Pretoria, 2018)
The purpose of the study was to understand school dropout in Zimbabwe from the perspectives of those with lived experiences of the phenomenon. As confirmed by literature, school dropout militates against efforts by schools and governments to increase graduation rates for individual and societal benefit. However, the major gap in literature which motivated this study was the glaringly missing voice of early school leavers (EScLs) themselves on the meaning they give to the school dropout phenomenon. Answers to the problem so far have largely come from secondary sources of data. The research was a qualitative case study, influenced by the interpretive philosophy. Bronfenbrenner’s Bioecological Theory of Human Development and Ajzen’s Theory of Planned Behaviour (TPB) formed the theoretical framework for the study. Twenty-two purposively sampled EScLs participated in focus group discussions, face-to-face interview and documented life stories. Research ethics were observed to ensure EScLs’ informed decision to participate in the study. The study established that school dropout could be best understood as a personal experience, having a greater impact at individual than societal levels. Findings revealed that both the process of dropping out and ultimately being an EScL are unpleasant and traumatic conditions, best understood as more of a psychological than an administrative problem. This results in a severed self-concept affecting an individual throughout life. It emerged from the study that loss, particularly through the death of biological parents, was the major underlying cause of school dropout, thus, pull factors take the toll over push and fall out factors. As solutions to the problem, the findings suggested a redefinition of vulnerability in response to the diverse and complex circumstances affecting learners. Findings also suggested the training of guidance and counselling teachers for effective intervention in learners’ problems. Education reforms and policy reviews that address inequity were recommended. Future studies could focus on in-depth analysis of pull factors in relation to school dropout.